Fatigue Performance of Reinforced Concrete T-Girders under Cyclic Loading. (25th March 2021) - Zhang, Jinquan; Bai, Bing; Zhang, Kechao; Cheng, Shoushan; Zhao, Shangchuan; Wang, Lei; Zhuang, Chenxu
Abstract : This paper examines the performance of reinforced concrete girders under cyclic loading. Seven T-girders were casted and tested. All girders were loaded under different constant cyclic loading in the midspan with the load ratio of 0.14∼0.23 and frequency of 3∼4 Hz. The study shows that the longitudinal reinforcement fracture is the main cause of girder rupture. And during cyclic loading, the concrete cracks, strains, and deflections generally indicate a "three-stage" law. The measured data were small but developed quickly in the initial stage. Thereafter, the degradation gradually stabilized and continued for a long time. In the final stage, the cracks, strains, and stiffness degradation developed sharply and the girders failed quickly. The duration of the stage is very short and may be difficult to be caught. For the life estimation, the longitudinal rebar S - N curve is fitted using different collected data. The results show that the curve is in good agreement with the corresponding data, which may be an excellent candidate for the evaluation of fatigue life.